Tinjauan atas Stevens-Johnson Syndrome dan Toxic Epidermal Necrolysis - Cinthia Christina Dewi (PT. Kalbe Farma Tbk., 2019)
Stevens-Johnson Syndrome dan toxic epidermal necrolysis (SJS/TEN) merupakan kasus jarang dengan kejadian 1-10 kasus per 1 juta kasus per tahun tetapi potensial mengancam nyawa. Etiologi tersering adalah reaksi hipersensitivitas terhadap obat. Patogenesis SJS/TEN belum sepenuhnya dimengerti. Gejala prodromal flu like symptom diikuti timbulnya bula dan epidermolisis. Komplikasi tersering adalah hipo- dan hiperpigementasi kulit serta pada mata. Tatalaksana terbaik adalah menghentikan obat yang disangka pencetus, terapi suportif berupa penggantian cairan dan elektrolit, terapi sistemik dan topikal, serta terapi untuk komplikasi pada mata.Stevens-Johnson syndrome and toxic epidermal necrolysis (SJS / TEN) is rare with an incidence of 1-10 cases per 1 million cases per year; but potentially life-threatening. The most common etiology is hypersensitivity reaction to drug. The symptoms begin with prodromal flu-like symptoms followed by the appearance of reddish lesions followed by bullae formation and epidermolysis. The most common complications are skin hypo- and hyperpigmentation and eye complications. The best management is to stop the presumptive drug, fluid and electrolye therapy and therapy for eye complications.